Determination of plasma-chlortetracycline (CTC) concentrations in grazing beef cattle fed one of four FDA approved free-choice CTC-medicated minerals. Issue 2 (20th April 2020) - Reppert, Emily J; Reif, Kathryn E; Montgomery, Shawnee R; Magnin, Geraldine; Zhang, Yuntao; Martin-Jimenez, Tomas; Olson, K C; Coetzee, Johann F
Abstract: Control of active bovine anaplasmosis in the United States is predicated on the use of chlortetracycline (CTC)-medicated feed throughout the vector season. However, data describing population pharmacokinetics of chlortetracycline in cows, on pasture, having free-choice access to CTC-medicated mineral for consecutive months is lacking. This study documented plasma-CTC concentrations in grazing cows during peak vector season in an anaplasmosis endemic herd. Each pasture was administered one of the four Food and Drug Administration approved CTC-medicated mineral formulations and were assigned as follows: 0.77 g/kg, Aureo Anaplaz C700 Pressed (Sweetlix Livestock Supplements, Mankato, MN); 5.5 g/kg, Purina Anaplasmosis Block (Purina Animal Nutrition, Gray Summit, MO); 6.6 g/kg, Stockmaster Aureo FC C6000 Mineral (Hubbard Feeds, Mankato, MN); 8.8 g/kg, MoorMan's Special Range Minerals AU 168XFE (ADM Animal Nutrition, Quincy, IL). Blood samples were collected monthly for determining plasma drug concentration by Ultra performance liquid chromatography (UPLC) and mass spectrometry. Continued plasma-CTC monitoring allowed for characterization of trends between treatment groups (pastures), age groups (<3 yr or >4 yr), and sampling times (June to October). Results indicate formulation (pasture) and time were significant factors affecting concentrations of CTC in plasma. Cows exposed to 5.5 g/kg block formulation recorded higher CTC plasma concentrations compared with other pasture groups ( P = 0.037). Plasma-CTC concentrations increased over time (month of measurement; P = 0.0005). Specifically, concentrations measured after 5 months of continuous CTC treatment were higher than those measured in earlier months.